LINKAGES IN CORPORATE SOCIAL RESPONSIBILITY INDICES AND MAJOR FINANCIAL MARKET INDICES. AN ARMA-APARCH APPROACH - LIU , Li-Lun; DIAZ, John Francis; IVAGOV , Esentur (Journal of Advanced Studies in Finance; Vol 5 No 2 (2014): JASF Volume V, Issue 2(10), Winter, 2014, 2014)
This research utilizes the Autoregressive Moving Average – Asymmetric Power Autoregressive Conditional Heteroscedasticity (ARMA-APARCH) in studying return and volatility relations among the three main Thomson Reuters Corporate Social Responsibility (CSR) Indices, and their major stock market indices counterparts.Using data from the post-Subprime Mortgage Crisis period, this study finds that both indices are not immune to negative shocks caused because coefficients of asymmetric volatility phenomenon is positive in all Thomson Reuters CSR and stock market indices. The lagged returns coefficient of the Wilshire Large Cap Total Market Index (WLCTM) has a negative effect on the future returns of the Thomson Reuters CRI US Large Cap ESG (TRESGUS). However, this is not the case with the Dow Jones Developed Markets Index (DJDM) and the Thomson Reuters Developed Markets ESG (TRESGDX) in which the lagged stock market index returns coefficient has positive effect on the CSR index returns. In terms of their volatility linkages, positive bilateral relations exist between the lagged volatility coefficients of WLCTM and TRESGUS, which suggests that the previous day’s heightened volatility in both indices will create a similar degree of fluctuations the next day on both the CSR and stock indices.However, only a unilateral lagged volatility effect is observed on the positive influence of the DJDM on TRESGDX.